PENGEMBANGAN SUPLEMEN BAHAN AJAR IPAS MENGUBAH BENTUK ENERGI KELAS IV SDN 36 PONTIANAK SELATAN - Husnani, Nurmi; Hartoyo, Agung; Kartono, Kartono (Universitas Tanjungpura, 2025)
According to experts in design, materials, language, and education, as well as students and teachers, the primary goal of the research was to create a product that could be used as a supplemental science lesson plan for the